Gambaran Variasi Serotipe Virus Dengue Pada Pasien Infeksi Dengue di Kota Semarang Tahun 2019 (Penelitian di Rumah Sakit dan Puskesmas Kota Semarang) - Rini Fajarani; Martini Martini; Mateus Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2020)
Background: In early 2019, the incidence of dengue infection in Semarang increasing than previous years and the Case Fatality Rate also increasing significantly to 3.88%. While the target of Case Fatality rate for dengue infection for every area is less than 1%. Increases cases at some area is related to replacement of serotypes circulation. Also, replacement of serotype circulation is likely to occur in areas with rapid urbanization. This study aims to describe the circulation of dengue virus serotypes in dengue infection patients in Semarang. Method: Type of this reasearch is descriptive observational with cross sectional design. Results: The most common virus serotypes were DENV-2 (80%), followed by mix infection of DENV-2 & DENV-3 (15%), and DENV-3 (5%). Based on host characteristics, more female patients (67.5%) were found compared to male patients. The incidence of dengue infection is dominated by adolescent group (17-25 years) Conclusion: DENV-2 is most found in patients with dengue infection in 2019. Female and adolescent age groups are the most commonly found in dengue patients.Keyword : Serotype, Virus, Dengue, DHF, Infection